2015
DOI: 10.1016/j.urology.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Physical and Emotional Discomfort Related to Urodynamic Testing: A Questionnaire-based Study in Men and Women With and Without Neurologic Conditions

Abstract: Objectives To determine predictors of physical and emotional discomfort associated with urodynamic testing in men and women both with and without neurologic conditions. Methods An anonymous questionnaire-based study completed by patients immediately after undergoing fluoroscopic urodynamic testing. Participants were asked questions pertaining to their perceptions of physical and emotional discomfort related to the study, their urologic and general health history, and demographics. Logistic regression was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…A urodynamic study (UDS) is invasive in nature and involves placement of urethral and rectal catheters, filling the bladder with fluid, voiding on demand in front of other people, and often the use of radiography, or fluoroscopy. In addition to painful sensations that may be associated with catheter positioning, invasive UDS may generate discomfort and embarrassment . Moreover, anxiety, physical distress, and other aspects of patient experience impact future compliance .…”
Section: Introductionmentioning
confidence: 99%
“…A urodynamic study (UDS) is invasive in nature and involves placement of urethral and rectal catheters, filling the bladder with fluid, voiding on demand in front of other people, and often the use of radiography, or fluoroscopy. In addition to painful sensations that may be associated with catheter positioning, invasive UDS may generate discomfort and embarrassment . Moreover, anxiety, physical distress, and other aspects of patient experience impact future compliance .…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies are wellā€tolerated, patients report emotional and physical discomfort especially during the placement of the catheters. Suskind et al found that 90% of patients who underwent UDS for the first time, reported that the study was the same as or better than expected . Also, they noted rectal catheter replacement as the worst part of the test .…”
Section: Discussionmentioning
confidence: 85%
“…Suskind et al found that 90% of patients who underwent UDS for the first time, reported that the study was the same as or better than expected. 1 Also, they noted rectal catheter replacement as the worst part of the test. 1 Several anesthetic treatments have been adapted to reduce the anxiety and pain associated with undergoing UDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, these patients may be best served by implementing "watchful waiting" due to the fact that additional treatment would not produce any benefits with respect to their symptoms. 58 55 "Emotional symptoms" convey to the patient's feeling to their disease.…”
Section: Historical Overview Of Hrqol and Its Implication On Turpmentioning
confidence: 99%